1998
DOI: 10.1111/j.1365-3156.1998.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between histopathological findings and phylogenetic divergence in Trypanosoma cruzi

Abstract: SummaryProblems have been raised by natural genetic diversity of Trypanosoma cruzi, the causal agent of Chagas' disease, and other protozoa in terms of both basic and applied science. T. cruzi manifests a great diversity of medical and biological properties which could be the origin of clinical variability in the disease. We propose possible correlations between genetic distances, or phylogenetic divergence, and histopathological data. To ascertain this aspect, 15 cloned stocks pertaining to three major clones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
1
17
1
3
Order By: Relevance
“…The relationship between pathogenicity and T. cruzi genotypes is still debated, with the hypothesis of genotype pathogenic specificity not being supported by the great diversity observed among strains within the same genotype (de Diego et al 1998) and by the differences in infectivity and immunopathology among strains belonging to a same DTU (Garzon et al 2005;Sanchez-Guillen Mdel et al 2006). As the variability of excreted-secreted proteins may be relevant to the biological heterogeneity of T. cruzi, we focused our study on the sequence variability and on the differential expression of Tc52 protein in epidemiologically relevant laboratory clones.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The relationship between pathogenicity and T. cruzi genotypes is still debated, with the hypothesis of genotype pathogenic specificity not being supported by the great diversity observed among strains within the same genotype (de Diego et al 1998) and by the differences in infectivity and immunopathology among strains belonging to a same DTU (Garzon et al 2005;Sanchez-Guillen Mdel et al 2006). As the variability of excreted-secreted proteins may be relevant to the biological heterogeneity of T. cruzi, we focused our study on the sequence variability and on the differential expression of Tc52 protein in epidemiologically relevant laboratory clones.…”
Section: Discussionmentioning
confidence: 98%
“…Studies trying to link the pathogenicity with parasite isolates or laboratory clones of different origins, based on their genetic or evolutionary distances, are controversial. While some studies reported a correlation between the genetic distances and the biological properties of the genotypes (Andrade and Magalhaes 1996;Laurent et al 1997;Revollo et al 1998;Toledo et al 2002), other authors demonstrated significant differences between genetically related T. cruzi clones, well documented in histopathology and other characteristics of murine experimental infections (Carneiro et al 1991;de Diego et al 1998). A few studies focused on the differential gene expression of some T. cruzi factors involved in key events of the parasite life cycle (Ruiz et al 1998;Weston et al 1999;Risso et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…The clinical manifestations and variations in the immune response observed during chagasic infection are not well understood but are believed to be associated with the host or parasite genetic variability. Several studies involving T. cruzi infection have confirmed that genetic diversity is correlated with intrinsic characteristics of the parasite such as virulence, drug resistance, parasitemia, tissue tropism, pathological alterations, capacity to induce host mortality, and pattern of humoral immune response (26,27,28,29). A further important aspect linked to genetic diversity is the susceptibility of parasites to the two pharmacological therapies that are currently available to treat human Chagas disease, namely, BZ (Roche, São Paulo, Brazil) and NF (Bayer, Leverkusen, Germany).…”
Section: Discussionmentioning
confidence: 99%
“…This clonal model predicts a parallel evolution between biological differences and genetic divergence among T. cruzi natural clones. Some results have shown a strong statistical linkage between genetic and biological differences using T. cruzi cloned stocks representing three or four major clonal geno- types of the parasite (Laurent et al 1997, Revollo et al 1998, Diego et al 1998, Toledo et al 2002, 2003.…”
mentioning
confidence: 99%